Utilizing COI gene for the identification of thirteen Hesperiidae butterflies and determining their genetic relationship - Akter, K; Meem, SM; Islam, S; Mamun, M A A; Abedin, M S; Borsha, F S; Ghosh, A; Hossain, Md Monwar (Journal of Biodiversity Conservation and Bioresource Management, 2023)
In the present study, the COI genes of thirteen species were sequenced, and NCBI GenBank homology searches of these species revealed significant similarity across diverse countries of origin. The sequences of thirteen species of hesperiid butterflies were then submitted to NCBI's GenBank, and assigned accession number. The average nucleotide composition of 585 bp of these genes was analyzed, and the results showed the mean base compositions of the COI sequences were 40.01% T, 16.10% C, 30.21% A, and 13.66% G. The present investigation revealed a significant preference for Adenine+Thymine (A+T), with a prevalence of 70.22%. Afterward, the genetic divergence among thirteen species of hesperiid was analyzed using the Kimura 2-parameter of the MEGA10 program, and the results indicated that the interspecific nucleotide divergence among thirteen species of hesperiid ranged from 0.0532 to 0.1790%. Moreover, a phylogenetic tree was constructed using the Neighbor-Joining (NJ) method, and the result revealed three clusters within the Pyrginae, Hesperiinae, and Coeliadinae subfamilies under the family Hesperiidae. The present investigation revealed Pyrginae as paraphyletic, while Coeliadinae was shown to be the sister group to Hesperiinae. As a final point, the analyses of the data support the following relationships: [(P. dan+T. japetus) + (P. guttata+P. bada+P. agna+B. cinnara+I. semamora+I. salsala+T. colon+U. folus + (O. angulatum)) + (B. oedipodea+S. gremius)]. The findings may be applicable to future research in the disciplines of molecular taxonomy to identify hesperiid species and may reveal a higher level of phylogenetic relationship among the subfamilies of Hesperiidae. Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 21-28